Micro-/Nano-Fiber Sensors and Optical Integration Devices - Li, Jin (Sensors (Basel, Switzerland), 2022)
Because of their strong surface evanescent field, micro-/nanofibers have been used to develop optical sensors and modulation devices with a high performance and integration [...].Because of their strong surface evanescent field, micro-/nanofibers have been used to develop optical sensors and modulation devices with a high performance and integration [...].